Vaginal Microbiome Components as Correlates of Cervical Human Papillomavirus Infection - Morales, Julia Andrade Pessoa [UNESP]; Marconi, Camila [UNESP]; El-Zein, Mariam; Ravel, Jacques; Pinto, Gabriel Victor da Silva [UNESP]; Silveira, Rosana [UNESP]; Lima, Moises Diogo de; Carvalho, Newton Sergio de; Alves, Rosane Ribeiro Figueiredo; Parada, Cristina Maria Garcia de Lima [UNESP]; Morais Leite, Sandra Helena; Villa, Luisa L. [UNESP]; et al. (Oxford Univ Press Inc, 2022)
Background Interplay between vaginal microbiome and human papillomavirus (HPV) remains unclear, partly due to heterogeneity of microbiota. Methods We used data from 546 women enrolled in a cross-sectional study in 5 Brazil. We genotyped vaginal samples for HPV and sequenced V3-V4 region of 16S rRNA gene for vaginal microbiome analysis. We used stepwise logistic regression to construct 2 linear scores to predict high-risk HPV (hrHPV) positivity: one based exclusively on presence of individual bacterial taxa (microbiome-based [MB] score) and the other exclusively on participants' sociodemographic, behavioral, and clinical (SBC) characteristics. MB score combined coefficients of 30 (of 116) species. SBC score retained 6 of 25 candidate variables. We constructed receiver operating characteristic curves for scores as hrHPV correlates and compared areas under the curve (AUC) and 95% confidence intervals (CI). Results Overall, prevalence of hrHPV was 15.8%, and 26.2% had a Lactobacillus-depleted microbiome. AUCs were 0.8022 (95% CI, .7517-.8527) for MB score and 0.7027 (95% CI, .6419-.7636) for SBC score (P = .0163). Conclusions The proposed MB score is strongly correlated with hrHPV positivity-exceeding the predictive value of behavioral variables-suggesting its potential as an indicator of infection and possible value for clinical risk stratification. This cross-sectional study demonstrated a strong correlation between vaginal microbiome components and cervical high-risk HPV positivity.
Keywords: Vaginal microbiome; HPV infection; high-risk HPV; 16S RNA sequencing